PENGARUH APLIKASI SPEECHNOTES TERHADAP KEMAMPUAN MENULIS CERITA PENDEK SISWA KELAS IX SMP NEGERI 1 PENANGGALAN - Ambarita, Surya Ningsih; Telaumbanua, Sadieli; Purba, Christin Agustina (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aims to explain the influence of applications Speechnotes on the ability to write short stories of Class IX students of SMP Negeri 1 Calendar for the 2024-2025 Academic Year. Apart from that, to explain students' perceptions in implementing the application Speechnotes towards learning to write short stories for Class IX students of SMP Negeri 1 Penaggalan for the 2024-2025 academic year. This research uses a Quasi Experimental method involving one group (one group), namely the experimental class. The population in this study were class IX students of SMP Negeri 1 Penanggalan from classes IX-1, IX-2, and IX-3. The total population is 90 students. Data analysis techniques for short story writing test results use statistical analysis. a) Descriptive analysis aims to determine a picture of students' abilities by testing frequency values ​​and average values. b) Inferential analysis or test. This test was carried out to determine the values ​​of normality, homogeneity and hypothesis testing. Qualitative techniques are used to analyze non-test data. This qualitative data was obtained from observation and interview data. The research results show that students' ability to write short stories after using the application Speechnotes or post test increased significantly. This can be seen from the student's lowest score being 73 and the highest 95. The average score of students after using this application or on post test is 85.13. This score exceeds the KKM score limit of 75. Apart from that, only 1 student has a score below the KKM and 1 student has the KKM limit score. After answering the hypothesis test with a calculated t value > t table, Ha is accepted with the hypothesis